2022
DOI: 10.1155/2022/3576419
|View full text |Cite
|
Sign up to set email alerts
|

Design of Shared Internet of Things System for English Translation Teaching Using Deep Learning Text Classification

Abstract: The purpose is to adapt to the current social development and promote the English translation teaching reform. Based on the theories of deep learning (DL), text classification (TC), and the Internet of Things (IoT), this work analyzes the current situation of English translation teaching. Additionally, 100 text categories are selected from the English text corpus of Northwestern Polytechnic University as the research objects. The data are classified by the DL-based TC method and analyzed by introducing the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The application of IOT technology to foreign language teaching is mainly done with the help of its video and audio sensors [20]. Among them, the video sensor records the data of foreign language learners' mouth patterns when practicing pronunciation, as shown in Equation ( 1), compares this video with the standard pronunciation video data already stored in the system, and measures the pronouncer's level by calculating the difference between them, and then achieves the function of correcting pronunciation.…”
Section: Methodsmentioning
confidence: 99%
“…The application of IOT technology to foreign language teaching is mainly done with the help of its video and audio sensors [20]. Among them, the video sensor records the data of foreign language learners' mouth patterns when practicing pronunciation, as shown in Equation ( 1), compares this video with the standard pronunciation video data already stored in the system, and measures the pronouncer's level by calculating the difference between them, and then achieves the function of correcting pronunciation.…”
Section: Methodsmentioning
confidence: 99%
“…He et al [24] have presented suggested the shared IoT system focused on teaching English translation with a DL-based TC. The goal was to further the reform of English translation instruction while adjusting to the present state of social improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The equation is the gradient of the weights between the 𝑖 𝑡ℎ input layer neuron and the 𝑗 𝑡ℎ hidden layer of the translation strategies for English language movies and 𝑡 𝑖 is the input of the 𝑖 𝑡ℎ neuron as presented in Equation (12). The weights all the connections will be updated based on the gradients of the weight as presented in the Equation (13).…”
Section: Figure 1: English Language Movie Translation Modelmentioning
confidence: 99%
“…Today's educators need to be flexible in their approach to teaching, familiar with cuttingedge information technology, and able to swiftly adapt to different contexts. The four main ways in which cloud computing is making a difference in college English classrooms are by raising students' awareness of the importance of active participation; removing physical barriers to learning; providing access to a wealth of educational and instructional resources; and fostering a multiplicity of interactions between students and teachers [12]. This is mostly because of how college-aged students' perspectives have shifted as a result of learning English in the cloud.…”
Section: Introductionmentioning
confidence: 99%